BA 285 - Business Relation in a Global Economy - Linn Benton Virtual College (2018)
An analysis of the behavior of humans as actors in a variety or organizational contexts and cultures, including group, inter-group, and individual behavior. A cross cultural perspective of organizational behavior is also examined, including the concepts of time-management, work ethic, teamwork, and verbal and non-verbal communication.